1979
DOI: 10.1136/hrt.42.5.587
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic effects of disopyramide in patients after open-heart surgery.

Abstract: SUMMARY Disopyramide phosphate was administered intravenously in a dose of 1-2 mg/kg body weight over one minute to nine patients after open-heart surgery and coronary artery bypass grafting. The haemodynamic changes were studied during and for 30 minutes after drug administration. Heart rate was unchanged throughout the study. During infusion the only significant changes were an increase in systemic blood pressure and systolic impedance signifying a direct increase in peripheral arterial resistance. Systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Furthermore, this inhibitory action of disopyramide may also be involved in more marked negative inotropic effects reported in patients with pre-existing left ventricular abnormalities (Hills et al, 1976;Jensen et al, 1976;Sutton, 1976;Davies et al, 1979;Hulting & Rosenhamer, 1979;Naqui et al, 1979;Scheinman et al, 1980;Gottdiener et al, 1983;Greene et al, 1983;Marrott et al, 1983;Cameron et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this inhibitory action of disopyramide may also be involved in more marked negative inotropic effects reported in patients with pre-existing left ventricular abnormalities (Hills et al, 1976;Jensen et al, 1976;Sutton, 1976;Davies et al, 1979;Hulting & Rosenhamer, 1979;Naqui et al, 1979;Scheinman et al, 1980;Gottdiener et al, 1983;Greene et al, 1983;Marrott et al, 1983;Cameron et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a negative inotropic effect of disopyramide has been identified in animal experiments (Nayler, 1979;Walsh & Horwitz, 1979;Abdollah et al, 1984;Beltrame et al, 1984) and has been detected by echocardiography (Martin et al, 1980;Pollick et al, 1982;Holt et al, 1983), radionuclide angiography (Wisenberg et al, 1984) and during cardiac catheterisation (Thadani et al, 1981) in normal volunteers. In some haemodynamic studies on patient groups, the effects of disopyramide on myocardial performance have been minimal (Marrott et al, 1976;Sutton, 1976), but in patients with preexisting left ventricular function abnormalities, negative inotropic effects are more marked (Hills et al, 1976;Jensen et al, 1976;Sutton, 1976;Davies et al, 1979;Hulting & Rosenhamer, 1979;Naqui et al, 1979;Scheinman et al, 1980;Gottdiener et al, 1983;Greene et al, 1983;Marrott et al, 1983;Cameron et al, 1984). However, the mechanisms of the negative inotropic effects of disopyramide have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…5) suggests that the pressure-reducing effect of disopyramide is not mainly caused by its negative inotropic action. It has been reported that disopyramide increases systemic resistance [7,26,27], while other negative inotropic drugs, such as [3-blocking agents and calcium inhibitors, do not show the same effect. Indeed, the systemic resistance increased in our study.…”
Section: Effects Of Disopyramide In Delaying the Onset Of Obstructionmentioning
confidence: 94%
“…In anaesthetized dogs, DP produces an increase in arterial blood pressure that is not blocked by phenoxybenzamine (Walsh & Horwitz, 1979). Haemodynamic studies in man have shown that DP increases peripheral vascular resistance and decreases cardiac output (Navqui et al, 1979). As DP has a negative inotropic effect, the elevation of arterial blood pressure may be due to an increase in peripheral vascular resistance.…”
mentioning
confidence: 99%
“…Discussion The intravenous injection of DP in patients without signs of cardiac failure produces an increase in diastolic and mean arterial pressure (Navqui et al, 1979). In anaesthetized dogs, DP produces an increase in arterial blood pressure that is not blocked by phenoxybenzamine (Walsh & Horwitz, 1979).…”
mentioning
confidence: 99%